CATEGORY SHIFTS IN BILINGUAL BOOK “LITTLE COMPANIONS” BY ARLEEN AARON RANDY - Turnip, Santika; Ambalegin, Ambalegin (SCIENTIA JOURNAL, 2019)
This descriptive qualitative research aims to find out the type of category shifts proposed by Catford in English-Indonesia bilingual book Little Companion (2017) written by Arleen Aaron Randy and the significant contribution of category shifts from source language to target language. The data were collected by using observation method and non-participatory technique. The data were analyzed by using translational identity method and translational competence in-dividing technique. There were four types of category shift found. Structure shift functioned to change in grammatical structure from source language to target language. Class shifts occurred when the translation equivalent of source language item was a member of different class of word, from noun to adjective, and clause to verb. Intra-system shift functioned to change the plural to singular. And unit shift was applied when the unit at one level in source language became different level in the target language. There were high level to lower level, and low level to higher level in unit shift. The significant contribution of category shifts in translating was to re-express the same meaning, to vary the translation way, to encourage social culture, to reveal the same meaning, and to get easily the result of translation shifts.